The bilateral onset of dilated blood vessels on the face in a pregnant patient - Ranjana Garg; Suresh K Veerabhadrappa; Vivek Vijay Gupta; Seema Yadav (Wolters Kluwer Medknow Publications, 2023)
Telangiectasias are superficial skin blood vessels arising from arterioles, venules, or capillaries. Arteriolar telangiectasias are small, bright red vessels which flush with the skin. While generally harmless, they can be a cosmetic concern. Diagnosis usually involves history, precise location assessment, clinical examination, and blood tests. Some cases may require a skin biopsy for underlying conditions. We present an unusual case of linear facial telangiectasia in a pregnant patient, attributed to increased vascularity and elevated estrogen levels. Unexpectedly, these lesions persisted post pregnancy. The initial diagnosis relied on chairside assessments, including diascopy tests and dermoscopy imaging. An attempt was made to address the cosmetic concerns with a 532-nm pulse diode laser treatment. However, this treatment was discontinued as the condition worsened after a few sessions, and the patient declined further attempts. Instead, she was advised to use high-SPF sunscreen and apply cosmetic products to conceal the lesions.